Prevalence of Diabetic Retinopathy in Nakhon Pathom Province - Sirimaharaj, Maytinee; Arame, Punyawee; Sumsawat, Piriya; Somboonthanakit, Sudawadee; Wongsawat, Warapat (Journal of Health Science of Thailand, 2017)
This retrospective study was aimed at examining the prevalence of diabetic retinopathy (DR) in DR screening program of Mettapracharak hospital (Wat Rai Khing) during June – December 2008. The fundi of all attended patients were captured in single field image using a non-mydriatic fundus camera. The photographs were reviewed by retinal specialists. A total of 3,128 diabetic patients who registered at 4 district hospitals in Nakhon Pathom province; Don Tum, Bhutthamonthon, Nakhon Chai Si and Sam Phran hospital were enrolled. Most patients were female (71.0%), aged more than 41 years (92.0%), affected with diabetes for 1-5 years (75.2%) and 55.9 percent had history of poorly controlled blood sugar level (≥ 130 mg%). Their diagnoses showed no diabetic retinopathy in 67.0 percent of the patients, nonproliferative DR in 20.4 percent, proliferative DR in 0.9 percent and 11.7 percent of the patients had poor visualization or too small pupils to get enough quality fundus photographs for reviewing. Diabetic macular edema was found in 10.5 percent of all patients who had DR. Most patients (76.4%) were advised to undergo regular eye examination, 6 percent was referred for laser photocoagulation or surgery and the rest (17.6%) was sent for further examination and investigation. The result showed that diabetes and its complications especially diabetic retinopathy were still one of the major health problems of Thailand. The DR screening using fundus photoghraphy was convenient, reliable and cost-effective leading to early diagnosis and lower the risk of visual loss in diabetic patients. All levels of health care workers were important in health education, organizing the screening program and operating the referral system for proper management of diabetic patients.